Estimation of Stiffness derivative for Ogives at Constant specific heat Ratio γ = 1.666 at Hypersonic Mach Numbers - et. al., Aysha Shabanaa, Shamitha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Specific heat ratios play an essential role in the design of an ogive of an aircraft, which in turn makes it a priority point in estimating the stiffness derivative, keeping in mind the stability of an airplane. One such attempt is made here where the study of stiffness derivative is done for specific heat ratio =1.666 for other than the air. In some cases, higher values of specific heat ratios become a priority to stimulate the flow. For δ angles from 50 to 300, results have been obtained. For pivot locations near the nose, the pitching moment assumes higher values as compared to the pivot position near the shoulder of the ogive. The stability derivatives attain negative values for h = 0.6, and its importance is maximum at h = 1.